Pengaruh Model Teaching Personal And Social Responsibility (TPSR) Terhadap Peningkatan Sikap Mandiri Dan Gotong Royong Siswa Kelas V Pada Materi Gotong Royong Di Lingkungan Sekitar - Lestari, Rahayu; Hakim, Abdul; Ramdan, Mohamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACTThis study explores the implementation of the Teaching Personal and Social Responsibility (TPSR) model as an instrument to strengthen the independent and cooperative dimensions of fifth-grade elementary school students. The primary focus of this research is directed at Pancasila Education materials using a qualitative method through a library research design. Through the analysis of various scientific literatures and curriculum documents, it was found that the TPSR model effectively increases student learning independence at the Self-Direction level through a controlled autonomy scheme. Additionally, the value of cooperation was successfully internalized through the Caring and Helping level, which proved capable of building positive social interactions and reducing conflict within group dynamics. The synthesis results emphasize that individual independence is a crucial prerequisite for creating synergistic collaboration. This study concludes that the integration of the TPSR model is a relevant pedagogical strategy to restore student character post-pandemic while comprehensively supporting the achievement of the Pancasila Student profile.